Bridewell Legal Advice Study: adopting a 'whole-systems' appraoch to police station legal advice - Kemp, Vicky (Legal Services Research Centre, 2013)
The Bridewell Legal Advice Study was intended to improve access to legal advice by basing duty solicitors in a large city centre police station. Implications for legal advice, for changing relations between the police and the defence, and in improving the pre-charge process were examined. The study examines issues concerning the take-up of legal advice, duration and case outcomes, as well as police disclosure and the quality of pre-charge decision-making. Also highlighted were issues concerning positive policing practices and implciations for using police custody as a form of social control.